2008
DOI: 10.1212/01.wnl.0000324414.12665.b0
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption and risk of subclinical brain abnormalities on MRI in older adults

Abstract: Objective: To investigate the association between fish consumption and subclinical brain abnormalities. Methods:In the population-based Cardiovascular Health Study, 3,660 participants age Ն65 underwent an MRI scan in 1992-1994. Five years later, 2,313 were scanned. Neuroradiologists assessed MRI scans in a standardized and blinded manner. Food frequency questionnaires were used to assess dietary intakes. Participants with known cerebrovascular disease were excluded from the analyses. Results:After adjustment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 43 publications
(55 reference statements)
4
62
0
1
Order By: Relevance
“…lar Health Study, which found that the consumption of fish at least 3 times a week based on dietary questionnaires was associated with a lower risk of subclinical vascular brain abnormalities. 24 Fatty acids are integral components of biological membranes, and influence membrane fluidity, ion transport, and other functions. 25 The neuronal cell membrane is no exception; the CNS has the highest concentration of phospholipids in the body.…”
Section: Discussionmentioning
confidence: 99%
“…lar Health Study, which found that the consumption of fish at least 3 times a week based on dietary questionnaires was associated with a lower risk of subclinical vascular brain abnormalities. 24 Fatty acids are integral components of biological membranes, and influence membrane fluidity, ion transport, and other functions. 25 The neuronal cell membrane is no exception; the CNS has the highest concentration of phospholipids in the body.…”
Section: Discussionmentioning
confidence: 99%
“…e1 The Cardiovascular Health Study (n 5 2,465, 59% women, average age 75 years) reported less likelihood of subclinical infarcts, defined as ischemic lesions $3 mm in diameter, for participants who ate fatty, nonfried fish more frequently. 26 In a previous study with 192 men and women (average age 78 years), the mean decrease in total brain volume was 20.45% and 20.98% per year in subjects without and with dementia, respectively, over an average of 2 years follow-up. 27 Interestingly, they also found that the slope of the cross-sectional relationship between age and brain volumes in subjects without dementia was similar to the longitudinal rate of change.…”
mentioning
confidence: 84%
“…It also seems to have beneficial effects in reducing myocardial infarction, but the effects on stroke is less clear [83,84]. Among older adults, modest consumption of fish (not fried fish) was associated with lower prevalence of subclinical infarcts and white matter abnormalities on magnetic resonance images [85]. These data support the benefit of lifestyle modification.…”
Section: Dietary Habitsmentioning
confidence: 90%